EVALUASI KINERJA PEGAWAI BAGIAN PENGADAAN BARANG/JASA UNTUK OPTIMALISASI PENGADAAN MELALUI E-PURCHASING : (STUDI KASUS DI LAYANAN PENGADAAN SECARA ELEKTRONIK KABUPATEN TEMANGGUNG) - Dewi Aryani Mitasari; Meidi Syaflan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The Goods/Services Procurement Section of Temanggung Regency Regional Secretariat is a government agency whose main task is to facilitate and assist all Regional Apparatus Organizations or Organisasi Perangkat Daerah (OPD) in Temanggung Regency. in the implementation of electronic Procurement Services at the Regional Secretariat of Temanggung Regency through e-purchasing are still not up to the planned target. The lack of willingness to conduct procurement through e-purchasing because they are still used to carry out procurement manually, the lack of human resources, there are also employees who feel that using e-purchasing still takes a lot of time since they also have to work in other units per the assignment letter given by superiors and the reason of inefficient implementation in e- Purchasing is shopping prices are becoming more expensive than the conventional ones, that is the problem that researchers found in this study. The purpose of this research is to identify the factors that impede employee performance in implementing e-purchasing in Temanggung Regency and to formulate strategies that need to be developed to optimize employee performance in implementing e-purchasing in Temanggung Regency. this study uses descriptive qualitative research carried out at LPSE Temanggung Regency. Researchers wish that this research can be useful theoretically, namely knowing the factors in employee performance in the implementation of Electronic Procurement in Temanggung Regency and can be some input for officials or officers at the Procurement Service Unit or Unit Layanan Pengadaan (ULP) in the scope of Temanggung Regency and will be practically useful for Regional Government, also can be a reference for government agencies in optimizing employee performance in the implementation of Electronic Procurement and can be a reference in the form of theoretical knowledge and concepts for further research related to Performance Improvement in the implementation of Electronic Procurement in other government agencies.